Semi-automated quantitation of mitophagy in cells and tissues - Montava-Garriga, Lambert; Singh, François; Ball, Graeme; Ganley, Ian G. (Mechanisms of ageing and development, 2020)
•The mito-QC reporter is a powerful model to monitor mitophagy in vitro and in vivo.•The mito-QC Counter is a new semi-automated tool to quantify mitophagy.•Mitophagy is induced in ARPE19 cells and varies in distinct skeletal muscle regions. Mitophagy is a natural phenomenon and entails the lysosomal degradation of mitochondria by the autophagy pathway. In recent years, the development of fluorescent pH-sensitive mitochondrial reporters has greatly facilitated the monitoring of mitophagy by distinguishing between cytosolic mitochondria or those delivered to acidic lysosomes. We recently published the mito-QC reporter, which consists of a mitochondrial outer membrane-localised tandem mCherry-GFP tag. This allows the quantification of mitophagy via the increase in red-only mCherry signal that arises when the GFP signal is quenched upon mitochondrial delivery to lysosomes. Here we develop a macro for FIJI, the mito-QC Counter, and describe its use to allow reliable and consistent semi-automated quantification of mitophagy. In this methods article we describe step-by-step how to detect and quantify mitophagy and show that mitophagy levels can be reliably calculated in different cell lines and under distinct stimuli. Finally, we show that the mito-QC Counter can be used to quantify mitophagy in tissues of mito-QC transgenic mice. We demonstrate that mitophagy levels in skeletal muscle correlates with glycolytic activity. Our present data show that the mito-QC Counter macro for FIJI enables the robust quantification of mitophagy both in vitro and in vivo.